Constitutionalizing Islamic Inheritance Law Through Progressive Legal Interpretation - Asrofi; Oyo Sunaryo Mukhlas; Ahmad Hasan Ridwan; Zulbaidah (As-Siyasi: Journal of Constitutional Law, 2026)
This article examines how the KHI (Compilation of Islamic Law) can acquire constitutional legitimacy in inheritance adjudication and how progressive law can operate as a disciplined method of constitutional interpretation. It employs normative legal research using statutory, conceptual, case, and limited comparative approaches. The analysis covers the KHI, constitutional and statutory norms, selected Supreme Court decisions on mandatory bequests, substitute heirs, marital property, and consensual distribution, as well as constitutional accommodation of religious law in Malaysia and England and Wales. The findings show that the KHI operates as institutionalized soft law with strong functional authority in the Religious Courts but incomplete formal and democratic legitimacy. This weakness creates risks for legal certainty, equality, property rights, procedural fairness, and accountability. Judicial practice has partially constitutionalized the KHI, yet relevant ratio decidendi are not consistently expressed through structured constitutional standards. The article therefore proposes directed constitutional progressivism, a three-layer model integrating constitutional supremacy, maqāṣid al-sharī‘ah, purposive interpretation, proportionality, and separation of powers. Its layers are simultaneous and mutually corrective: constitutional alignment in adjudication, harmonization of jurisprudence through transparent and reviewable reasoning, and participatory legislative strengthening that preserves controlled judicial flexibility. The model repositions progressive law within constitutionalism and supplies operational standards for judges, the Supreme Court, and legislators to protect substantive justice without sacrificing legal certainty or the normative identity of Islamic inheritance law